Frequency upconversion in rare-earth doped fluoroindate glasses - Araújo, Cid B. de; Maciel, Glauco S.; Menezes, Leonardo de S.; Rakov, Nikifor; Falcão-Filho, Edilson L.; Jerez, Vladimir A.; Messaddeq, Younes [UNESP] (Cellule MathDoc/Centre Mersenne, 2002)
We present recent results on frequency upconversion (UPC) obtained in fluoroindate glasses (FIG) doped with Ho3+, Tm3+ and Nd3+ ions and codoped with Pr3+/Nd3+ and Yb3+/Tb3+ ions. The results for the Ho3+-doped samples show strong evidence of energy transfer (ET) between Ho3+ ions resonantly excited at 640 nm. The origin of the blue-green upconverted fluorescence observed was identified and the dynamics of the signals revealed the pathways involved in the UPC process. In the case of Tm3+-doped FIG, the samples were resonantly excited at 650 nm and the main mechanism that contributes for the red-to-blue upconversion is excited-state absorption (ESA). The FIG samples codoped with Pr3+/Nd3+ were excited at 588 nm in resonance with transitions starting from the ground state of the Nd 3+ and the Pr3+ ions. It was observed that the presence of Nd3+ ions enhanced the Pr3+ emission at 480 nm by two orders of magnitude. Multiphonon (MP)-assisted upconversion is also discussed for Nd3+-doped FIG pumped at 866 nm. Emission at 750 nm with a peculiar linear dependence with the laser intensity was observed and explained. A rate-equation model that includes MP absorption via thermally coupled electronic excited states of Nd3+ was developed and describes well the experimental results. The role played by effective phonon modes is clearly demonstrated. MP-assisted UPC process was also studied in Yb3+/ Tb3+-codoped FIG samples excited at 1064 nm, which is off-resonance with electronic transitions starting from the ground state. It was determined that the mechanism leading to Tb3+ emission in the blue is due to ET from a pair of excited Yb3+ ions followed by ESA in the Tb 3+ ions. © 2002 Académie des sciences/Éditions scientifiques et médicales Elsevier SAS.
Keywords: Fluoroindate glass; Frequency upconversion; Rare-earth ions